Creating Study-Specific Tools to Increase Community and Student Engagement. (1st December 2021) - Dunbar-Wallis, Amy; Jaeger, Deidre; Suding, Katharine; Littman, Paige; Baumgartner, Laura; Prater, Maggie; Schuenemeyer, Adalyn; Tuff, Kika; Hogstad, Amelia Brackett; Alam, Irfanul; Corwin, Lisa
The Boulder Apple Tree Project (BATP) at the University of Colorado agglomerates ecological, historical, and genetic information regarding apple trees in Boulder County, Colorado with the assistance of community members, undergraduates, and researchers. Our goal is to map and measure historic apple trees in Boulder to find the varieties that were planted as part of Boulder's unique apple industry in the early 1900s. These trees are of interest to historians, horticulturalists, cider makers, and ecologists wishing to preserve heritage varieties and to better understand the ecology of urban apples. Combining the efforts of the campus community with the contributions of community members has allowed us to locate and measure more than 700 individual trees in the past four years, which are displayed in the interactive map showing locations and morphological measures of each tree. Harnessing this interest in local apple trees has allowed the project to provide educational opportunities to the community and undergraduates regarding the services that urban trees provide. Undergraduate computer science students built the interactive map to display tree locations and a mobile phone app designed for collecting and visualizing data in real time. These digital products will allow the broader population to engage in locally relevant research. This paper is a case study that focuses on curricular and extracurricular engagement of undergraduate students, application design, and the contributions of these efforts to the scientific community.